Pengembangan Industri Kreatif Berbasis Produk Hasil Diversifikasi Daging dan Telur Itik Cihateup di Tasikmalaya - Kusmayadi, Andri (Institut Agama Islam Negeri Bengkulu, 2020)
Creative industries are one of the means of community innovation in developing their interests and talents in various fields. Creative industries engaged in food processing based on food diversification are still limited. Cihateup Ducks as a local commodity Cihateup Hamlet as one of the regions in Tasikmalaya Regency has potential as a producer of meat and eggs that still has a low economic value compared to meat and egg products that have been processed into fast food. The purpose of this community service program is to process local potential in the form of Cihateup duck meat and eggs into various processed products that are preferred by the community and to develop creative industries engaged in food diversification to increase people's income. The implementation of the community service program was conducted from January to October 2019 in the Cihateup Hamlet, Sukanagalih Village, Rajapolah District, Tasikmalaya Regency. The method applied is counseling, mentoring and training for farmer / livestock groups. The results of this program are increasing people's income and the creation of a creative industry.